2022
DOI: 10.1017/dmp.2022.192
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Psychological Problems Among the Health Care Workers Across Two Waves of SARS-CoV-2 (COVID-19) Pandemic: An Observational Study from India

Abstract: Objective: Literature investigating the change in psychological problems of the healthcare workers (HCWs) throughout the COVID-19 pandemic is lacking. We aimed at comparing the psychological problems and attitudes towards work among them over two waves of the COVID 19 pandemic in India. Methods: A survey was conducted involving HCWs (n=305, first-wave, 2020; n=325, second wave, 2021). Participants’ demographic- and professional- and psychological characteristics (using attitude towards C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…This is consistent with the findings of a recent Italian study showing that fear of COVID-19, its consequences, and the likelihood of isolation are greater in young adults compared to older people, which could be explained by lower levels of anxiety, depression, and stress and greater preventive measures in older people [5]. Education level has a significant influence on the intention to be vaccinated, which has also been confirmed by other studies performed in different phases of the pandemic [46][47][48][49][50][51][52][53].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with the findings of a recent Italian study showing that fear of COVID-19, its consequences, and the likelihood of isolation are greater in young adults compared to older people, which could be explained by lower levels of anxiety, depression, and stress and greater preventive measures in older people [5]. Education level has a significant influence on the intention to be vaccinated, which has also been confirmed by other studies performed in different phases of the pandemic [46][47][48][49][50][51][52][53].…”
Section: Discussionsupporting
confidence: 92%
“…HCWs reported the greatest psychological distress at the beginning of the pandemic, when the country went into lockdown, classes were held remotely, children were cared for at home, many people worked from home, and HCWs were instructed to be present at work. Similarly, research from India comparing two phases of the pandemic reported that HCWs were less affected by psychological impacts during the second phase [49]. A statistically significantly lower psychological burden in the third survey period than in the first survey period could be explained by psychological resilience.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Some studies had focused on a single second wave of infection [ 17 , 18 ]. A study comparing two waves of infection in India reported that HCW were less affected by psychological impacts during the second wave [ 19 ], but two Italian studies comparing psychological stress in the first and second waves reported no significant differences between the two waves [ 20 , 21 ]. These findings leave questions such as, if in different countries, with a variety in backgrounds or influencing factors, how can the negative psychological effects and severity in HCW during different waves of the pandemic differ?…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other studies have found that depressive symptoms occur more often in women than in men [22], the prevalence of depression among female physicians is about 1.5 times higher than that of men and the prevalence of severe depression is about eight times higher [23]. The results of domestic studies indicate that the mental health quality of female medical personnel is lower than that of men [24][25][26].…”
Section: Analysis Of the Influencing Factors On The Mental Health Of ...mentioning
confidence: 99%